Cognition as a Subject of Research in Cognitive Science; Procedia - Social and Behavioral Sciences; Vol. 154 : Proceedings of The XXV Annual International Academic Conference, Language and Culture, 20-22 October 2014 - Chernikova I. V. Irina Vasilievna (2014, 2014)
Title screen